A phase 1 trial of temsirolimus and intensive re‐induction chemotherapy for 2nd or greater relapse of acute lymphoblastic leukaemia: a Children's Oncology Group study (ADVL1114). (14th March 2017) - Rheingold, Susan R.; Tasian, Sarah K.; Whitlock, James A.; Teachey, David T.; Borowitz, Michael J.; Liu, Xiaowei; Minard, Charles G.; Fox, Elizabeth; Weigel, Brenda J.; Blaney, Susan M.
Summary: The phosphatidylinositol 3‐kinase (PI3K)/mammalian (or mechanistic) target of rapamycin (mTOR) signalling pathway is commonly dysregulated in acute lymphoblastic leukaemia (ALL). A phase 1 trial of the mTOR inhibitor temsirolimus in combination with UKALL R3 re‐induction chemotherapy was conducted in children and adolescents with second or greater relapse of ALL. The initial temsirolimus dose level (DL1) was 10 mg/m 2 weekly × 3 doses. Subsequent patient cohorts received temsirolimus 7·5 mg/m 2 weekly × 3 doses (DL0) or, secondary to toxicity, 7·5 mg/m 2 weekly × 2 doses (DL‐1). Sixteen patients were enrolled, 15 were evaluable for toxicity. Dose‐limiting toxicity (DLT) occurred at all three dose levels and included hypertriglyceridaemia, mucositis, ulceration, hypertension with reversible posterior leucoencephalopathy, elevated gamma‐glutamyltransferase or alkaline phosphatase and sepsis. The addition of temsirolimus to UKALL R3 re‐induction therapy resulted in excessive toxicity and was not tolerable in children with relapsed ALL. However, this regimen induced remission in seven of fifteen patients. Three patients had minimal residual disease levels <0·01%. Inhibition of PI3K signalling was detected in patients treated at all dose levels of temsirolimus, but inhibition at an early time point did not appear to correlate with clinical responses at the end of re‐induction therapy.